Stronger transcription regulatory circuit of HIV-1C drives the rapid establishment of latency with implications for the direct involvement of tat - Chakraborty, Sutanuka; Kabi, Manisha; Ranga, Udaykumar (Journal of Virology, 2020)
The magnitude of transcription factor binding site variation emerging in HIV-1 subtype C (HIV-1C), especially the addition of NF-kappa B motifs by sequence duplication, makes the examination of transcriptional silence challenging. How can HIV-1 establish and maintain latency despite having a strong long terminal repeat (LTR)? We constructed panels of subgenomic reporter viral vectors with varying copy numbers of NF-kappa B motifs (0 to 4 copies) and examined the profile of latency establishment in Jurkat cells. Surprisingly, we found that the stronger the viral promoter, the faster the latency establishment. Importantly, at the time of commitment to latency and subsequent points, Tat levels in the cell were not limiting. Using highly sensitive strategies, we demonstrate the presence of Tat in the latent cell, recruited to the latent LTR. Our data allude, for the first time, to Tat establishing a negative feedback loop during the late phases of viral infection, leading to the rapid silencing of the viral promoter. IMPORTANCE Over the past 10 to 15 years, HIV-1 subtype C (HIV-1C) has been evolving rapidly toward gaining stronger transcriptional activity by sequence duplication of major transcription factor binding sites. The duplication of NF-kappa B motifs is unique and exclusive to HIV-1C, a property not shared with any of the other eight HIV-1 genetic families. What mechanism(s) does HIV-1C employ to establish and maintain transcriptional silence despite the presence of a strong promoter and concomitant strong, positive transcriptional feedback is the primary question that we attempted to address in the present manuscript. The role that Tat plays in latency reversal is well established. Our work with the most common HIV-1 subtype, HIV-1C, offers crucial leads toward Tat possessing a dual role in serving as both a transcriptional activator and repressor at different phases of viral infection of the cell. The leads that we offer through the present work have significant implications for HIV-1 cure research.
Keywords: HIV-1C; latency; LTR; NF-kappa B; positive feedback; Tat